HISTORY OF THE DEVELOPMENT OF RADIODIAGNOSIS AT THE RUSSIAN RESEARCH CENTER OF ROENTGENOLOGY AND RADIOLOGY: ON THE OCCASION OF THE 90TH ANNIVERSARY OF ITS FOUNDATION - V. A. Solodkiy; P. M. Kotlyarov; N. V. Nudnov (Вестник рентгенологии и радиологии)
The paper describes the history of the Russian Research Center of Roentgenology and Radiology set up 90 years ago, the main advances of the researchers of the Institute in roentgenology and radiodiagnosis in historical perspective – from the last century up to the present day. It gives a brief list of the most important procedures and publications on radiodiagnosis, which have been developed and published by the Institute’s researchers.